2020
DOI: 10.1097/dcr.0000000000001612
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal Anastomoses in Minimally Invasive Right Colectomies Are Associated With Fewer Incisional Hernias and Shorter Length of Stay

Abstract: BACKGROUND: Intracorporeal anastomosis is associated with several short-term benefits. However, it is a technically challenging procedure with potential risk OBJECTIVE: The purpose of this study was to investigate differences in short-term complications and long-term incisional hernia rates after robotic right colectomy with intracorporeal versus extracorporeal anastomoses and standardized extraction sites. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
2
38
2
Order By: Relevance
“…The shorter LOS represents an overall better recovery after surgery with the IA method, which includes less wound pain, less stress on the bowel, and better recovery of bowel function. Many systemic reviews and meta-analyses have demonstrated similar findings [ 22 27 ]. The IA method has the following advantages: lower analgesic use, faster time to bowel movement and flatus passage, shorter time to solid food intake, and shorter length of hospitalization.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The shorter LOS represents an overall better recovery after surgery with the IA method, which includes less wound pain, less stress on the bowel, and better recovery of bowel function. Many systemic reviews and meta-analyses have demonstrated similar findings [ 22 27 ]. The IA method has the following advantages: lower analgesic use, faster time to bowel movement and flatus passage, shorter time to solid food intake, and shorter length of hospitalization.…”
Section: Discussionmentioning
confidence: 60%
“…The IA method has the following advantages: lower analgesic use, faster time to bowel movement and flatus passage, shorter time to solid food intake, and shorter length of hospitalization. The postoperative complications were comparable between the two methods [ 7 , 8 , 10 , 24 27 ].…”
Section: Discussionmentioning
confidence: 97%
“…The shorter LOS represents an overall better recovery after surgery with the IA method, which includes less wound pain, less stress on the bowel, and better recovery of bowel function. Many systemic reviews and meta-analyses have demonstrated similar ndings [22][23][24][25]. The IA method has the following advantages: lower analgesic use, faster time to bowel movement and atus passage, shorter time to solid food intake, and shorter length of hospitalization.…”
Section: Discussionmentioning
confidence: 79%
“…The IA method has the following advantages: lower analgesic use, faster time to bowel movement and atus passage, shorter time to solid food intake, and shorter length of hospitalization. The postoperative complications were comparable between the two methods [7,8,[22][23][24][25][26].…”
Section: Long-term Postoperative Outcomesmentioning
confidence: 78%
“…Robotic surgery eases suturing and enables reinforcement of the stapled anastomosis, facilitating intracorporeal anastomoses [2]. The latter have been associated with reduced incidence of hernia and faster recovery [3]. Drawbacks of the robotic approach are the associated costs and longer operative time [4].…”
mentioning
confidence: 99%